Enhancing smallholder agricultural production through sustainable use of shallow groundwater in the Borkena Catchment, Awash River Basin, Ethiopia - Ebrahim, Girma Yimer; Taye, Meron Teferi; Seid, Abdulkarim; Tekleab, S. (IWA Publishing, 2024)
With increasing shallow groundwater use for agricultural purposes, understanding the spatiotemporal variability in recharge rates, storage capacity, and its interaction with surface waters becomes crucial for its sustainable management. An integrated SWAT–MODFLOW model is developed to assess shallow groundwater availability in the Borkena catchment. The model is calibrated using streamflow and static groundwater level data. Results show that groundwater recharge in the catchment is 85 mm/a, representing 11% of the mean annual rainfall. Shallow groundwater resources exist across nearly 42% of the Borkena catchment. The percentage of shallow groundwater withdrawal to groundwater recharge is very low (0.1%), signifying the potential for increased shallow groundwater development. However, caution must be taken as its uncontrolled expansion may result in a high risk of depletion. This integrated modeling is one of the few efforts conducted to provide important information regarding shallow groundwater potential in the Borkena catchment, which is essential for the resilience of small-scale producers in the continued growing water demand and climate change.